Devising a procedure for substantiating the type and volume of redundant structural-functional elements of reconnaissance-firing systems - Maistrenko, Oleksandr; Karavanov, Oleksandr; Riman, Oleksii; Kurban, Volodymyr; Shcherba, Andrii; Volkov, Ihor; Kravets, Taras; Semiv, Galina (Eastern-European Journal of Enterprise Technologies, 2021)
This paper proposes an algorithm for substantiating the type and volume of redundant structural and functional elements of reconnaissance-firing systems, taking into consideration the operational patterns of such systems. Underlying this algorithm is the combination of survivability assessment methods and reliability assessment methods. Such an arrangement aimed to improve the efficiency of the application of these methods and reduce uncertainty in the calculations. The results from calculating an example of the application of a procedure for substantiating the type and volume of redundant structural and functional elements of reconnaissance-firing systems have been analyzed. The analysis of the results shows that the set task is fulfilled, in particular the specified probability of trouble-free functioning of a reconnaissance-firing system, with a combined type of redundancy. Moreover, it implies giving preference to passive redundancy, using active one only to critical elements – individual functional elements of the control subsystem. The advantage of a mixed type of redundancy over a passive redundancy is 28 %. In addition, it has been established that the multiplicity of redundancy, for accepted conditions, should not be lower than 2. A procedure for substantiating the type and volume of redundant structural and functional elements of reconnaissance-firing systems has been devised, taking into consideration the operational patterns of such systems. The specified procedure includes an algorithm, as well as methods for assessing survivability and methods for assessing the reliability of functioning. This procedure was tested for feasibility by considering an example of justifying the type and volume of redundant structural and functional elements of reconnaissance-firing systems that produced an adequate result. The result has been confirmed by the practical application of reconnaissance-firing systems in recent armed conflicts